(untitled) (Global Journal of Science Frontier Research, 2012)
The present study was conducted for the time period of one year (April, 2009- March 2010) with an aim to find out the physico-chemical nature of water at different sites of River Jehlum in order to access the physical properties and chemical nature of its water and the impact of site/s on their concentration. Three sites were selected for the study purpose and the samples were collected on monthly bases. The samples thus collected were processed for the detection of metals with their relative concentrations following the standard methods. It was observed that the concentration of these metals was varying with respect to the collection sites, so was the case with respect to its physical nature. Also it was observed that there was a difference in concentration of these elements at different sites when compared among them selves. The data of physico-chemical nature of water of river Jehlum obtained during the study have been mentioned in Table 1. Furthermore it was also observed that concentration of some of these elements was more than the permissible limits as recommended by WHO which could have a definite impact on life. Keeping the same in view the present study was taken into consideration in which an attempt was made to access the water quality of River Jehlum and it is believed that this study would be helpful in formulating control strategy in near future.